The Necromancer - Scott, Michael, 1959- (Scott, Michael, 1959- Secrets of the immortal Nicholas Flamel ;, 2019)
Nicholas Flamel and teenaged twins Josh and Sophie Newman return to San Francisco where a weakened Flamel reunites with his wife, Perenelle, hoping to use his remaining power to prevent the monsters on Alcatraz Island from escaping. Meanwhile, Dr. John Dee and Machiavelli continue to seek power and the twins desperately try to determine who they can trust as they search for Scatty and an immortal who can teach Josh the magic of fire.